The Impact of Helicobacter pylori Urease upon Platelets and Consequent Contributions to Inflammation - Scopel-Guerra, Adriele; Olivera-Severo, Deiber; Staniscuaski, Fernanda; Uberti, Augusto F.; Callai-Silva, Natália; Jaeger, Natália; Porto, Bárbara N.; Carlini, Celia R. (Frontiers in Microbiology, 2017)
Gastric infection by Helicobacter pylori is considered a risk factor for gastric and duodenal cancer, and extragastric diseases. Previous data have shown that, in a non-enzymatic way, H. pylori urease (HPU) activates neutrophils to produce ROS and also induces platelet aggregation, requiring ADP secretion modulated by the 12-lipoxygenase pathway, a signaling cascade also triggered by the physiological agonist collagen. Here we investigated further the effects on platelets of recombinant versions of the holoenzyme HPU, and of its two subunits (HpUreA and HpUreB). Although HpUreA had no aggregating activity on platelets, it partially inhibited collagen-induced aggregation. HpUreB induced platelet aggregation in the nanomolar range, and also interfered dose-dependently on both collagen- and ADP-induced platelet aggregation. HPU-induced platelet aggregation was inhibited by antibodies against glycoprotein VI (GPVI), the main collagen receptor in platelets. Flow cytometry analysis revealed exposure of P-selectin in HPU-activated platelets. Anti-glycoprotein IIbIIIa (GPIIbIIIa) antibodies increased the binding of FITC-labeled HPU to activated platelets, whereas anti-GPVI did not. Evaluation of post-transcriptional events in HPU-activated platelets revealed modifications in the pre-mRNA processing of pro-inflammatory proteins, with increased levels of mRNAs encoding IL-1β and CD14. We concluded that HPU activates platelets probably through its HpUreB subunit. Activation of platelets by HPU turns these cells into a pro-inflammatory phenotype. Altogether, our data suggest that H. pylori urease, besides allowing bacterial survival within the gastric mucosa, may have an important, and so far overlooked, role in gastric inflammation mediated by urease-activated neutrophils and platelets.